Combination of Right Nephrectomy and Total Pancreaticoduodenectomy for von Hippel-Lindau Disease - Arkadopoulos, Nikolaos; Karapanos, Konstantinos; Stafyla, Vaia; Yiallourou, Anneza; Koureas, Andreas; Kondi-Pafiti, Agathi; Smyrniotis, Vassilios (JOP. Journal of the Pancreas, 2010)
Context Von Hippel-Lindau disease is an inherited syndrome of multiorgan neoplasia caused by a germline mutation in the von Hippel-Lindau gene and can include central nervous system tumors, renal cell carcinomas and benign pancreatic cystic tumors. Case report We report the case of a 56-year-old patient who had a past history of cerebellar hemangioblastoma and presented with abdominal pain. Imaging revealed renal tumors and multiple pancreatic tumors which caused duodenal and pancreatic duct compression. The patient was treated with a combination of radical right nephrectomy, total pancreaticoduodenectomy and splenectomy. Pathology identified a multifocal unilateral clear cell renal carcinoma which interestingly coexisted with multiple large pancreatic serous microcystic adenomas with infiltration of the fibrous capsule. Conclusion In past cases of von Hippel-Lindau disease, pancreatic adenomas with malignant transformation have not been reported. In our case, the infiltration of the fibrous capsule by parenchymal cells may indicate malignant transformation. Image: Section of serous microcystic adenoma in the pancreatic head.